THE CONTENTS OF GEOSCIENCES IN THE GEOGRAPHY DISCIPLINE: ANALYZING THE FIRST YEARS OF FUNDAMENTAL EDUCATION - Silva, Cláudia Patrícia Araújo e; Souza, Raquel Franco de (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.994, 2020)
In elementary school in Brazil the contents of geosciences are mainly distributed in the disciplines of science and geography. However, there is a greater focus of those contents from Elementary School II on. This study then sought to map the contents of geosciences in the Geography Textbooks of the Elementary School I, used in the public-school system of Natal City, in order to assess their presence in this cycle of education. The contents were identified and quantified through a count that considered ¼ page increments. The quantification of the contents was also made considering the Thematic Units proposed by the Common National Curricular Base. The results showed the presence of geosciences contents in books from the 1st to the 5th grade, more concentrated from the 3rd grade on, highlighting the 4th grade of Elementary School I. It also identified the landscape theme as one of the structuring axes for the teaching of geoscientific contents.